Impact of Empowerment on Women’s Livelihood in Oyo State, Nigeria - Fajobi, Deborah Tosin; Jubreel , Olasunmbo Kafilat; Ojediran, Janet Temitope; Adeomi, Damilola Toluse (PT. Riset Press International, 2025)
Women’s empowerment plays a vital role in driving economic and social development, especially in agriculturally driven communities. In Nigeria, despite women's substantial contributions to agriculture and household welfare, gender-based constraints persist—limiting their access to productive resources, credit, and decision-making. This study explores the impact of women’s empowerment programs on livelihood outcomes in Oyo State, Nigeria. It specifically examines women’s participation in empowerment initiatives, assesses the relationship between empowerment indicators and livelihood improvements, and identifies barriers to effective participation. A cross-sectional design was employed, drawing primary data from 100 respondents—including beneficiaries of the Women Development Fund (WDF) and key informants—through structured questionnaires, interviews, and document reviews. Data were analyzed using IBM SPSS Version 25. Descriptive statistics (frequencies and percentages) and inferential methods such as multiple regression and chi-square tests were applied to assess relationships among variables and test hypotheses. The results showed that participation in empowerment programs significantly improved women’s access to credit (95.6%), savings (90.0%), and income-generating opportunities (97.8%). Positive livelihood outcomes included increased income (98.9%), business expansion (97.8%), property ownership (74.7%), better healthcare access (96.7%), and improved food security (95.6%). Regression results revealed that increased income, property ownership, business growth, and decision-making autonomy significantly influenced women’s empowerment at the 1% significance level (p < 0.01). Empowerment programs substantially enhance women’s economic independence and household welfare. Nonetheless, barriers such as limited education, financial exclusion, and cultural norms hinder full participation. Addressing these through improved financial inclusion, supportive policies, and capacity-building initiatives is essential to unlocking the full potential of women in rural development and ensuring sustainable livelihood outcomes.